Improving the Supply Chain Performance of an Electronic Product-Manufacturing Organisation Using DMAIC Approach. Issue 1 (31st December 2022) - Makinde, Olasumbo; Selepe, Refentse; Munyai, Thomas; Ramdass, Kem; Nesamvuni, Alufeli
Abstract: With an ever-growing demand for electronic products around the globe, electronic product-manufacturing organisations are seeking suitable strategies to improve the efficiency of their supply chain processes. Hence, this study seeks to reduce process wastes and exploit bottlenecks present within the supply chain processes of an electronic product-manufacturing organisation. In light of this, lean supply chain strategies premised on the DMAIC methodology were unveiled and validated using a discrete-event simulation approach. We value streamed the supply chain system of an electronic product manufacturing organisation, identified the root causes of the process wastes and inefficiencies present in the organisation's supply chain and thereafter, identified suitable strategies capable of eliminating these process wastes and inefficiencies based on experts' opinions obtained during a focus group discussion forum. As a result of this exercise, three types of process wastes were identified and reduced. The simulation results of this study revealed that the idling time experienced at the workstations, and WIP (Work-In-Progress) inventories present within the supply chain system of this organisation, would be reduced by 7.6% and 81.41% respectively while the overall workstations utilisation would be improved by 9.32%, if the supply chain improvement strategies proposed by the authors are implemented at the electronic product-manufacturing organisation considered in this study. In addition, the total non-value added time would also reduce by 63.89 days, thereby having a potential of improving the throughput and the process cycle efficiency of the supply chain system proposed for use, to the organisation by 63% and 8.82%, respectively.